Improved embryo survival following follicular drainage of subordinate follicles for twin pregnancy prevention in bi-ovular dairy cows - Irina GARCIA-ISPIERTO; Fernando LÓPEZ-GATIUS (The Society for Reproduction and Development, 2019)
To prevent twin pregnancies in cattle, a simple transvaginal device can be used for follicular drainage. This study examines embryo survival following follicular drainage of the smaller pre-ovulatory follicle at timed artificial insemination (AI) in cows with a pre-ovulatory follicle in each ovary. The study groups established were a control group of 289 monovular cows, a non-drainage group of 114 bi-ovular cows and a follicular drainage group of 113 bi-ovular cows. All cows undergoing drainage developed a corpus luteum (CL) in the drained ovary. Pregnancy loss was recorded 56 days post-AI in 19.5% of the 149 cows that became pregnant. Pregnancy loss in the drainage group cows not suffering heat stress (3.8%) was significantly lower (P < 0.05) than in control non-heat stressed cows (20.9%) and heat-stressed non-drainage group cows (25%). Results indicate that CL induction by follicular drainage for twin pregnancy prevention may reduce the incidence of pregnancy loss.